High-Frequency Ultrasonography As An Innovative Diagnostic Method in Dermatology - Aneta Rasińska; Piotr Rzyczniok; Anna Rzyczniok; Weronika Rasińska; Justyna Jachimczak; Filip Grydź; Joanna Filipow; Anna Rebizak; Paulina Bala; Aneta Rostkowska; Sebastian Kupisiak; Natalia Pasierb; et al. (Quality in Sport)
Ultrasonography is now a standard, non-invasive imaging technique used in many areas of medical diagnostics. Currently it is also an important tool in the diagnosis of skin diseases. In clinical practice, High Frequency Ultrasonography (HFU) is used more and more often because it has proved to be a valuable diagnostic tool for assessing the condition of skin tissue. The physical conditions of  HFU make it possible  to estimate the parameters of the skin structure, such as thickness and echogenicity (a feature related to the center) of its layers in relation to the surrounding tissues. Therefore, HFU allows to obtain information concerning the condition of the examined area of the skin., the rate of lession development and the effectiveness of implemented theraphy. HFU is applied in the imaging of focal skin lesions, including melanoma, basal-cell carcinoma, inflammatory skin diseases, diseases associated with its thickening and in aesthetic medicine and cosmetology. The aim of this chapter is to familiarize the reader interested in dermatology and in particular diagnostics in this field, the possibilities associated with the use of HFU.